ACCESSIBILITY OF DISABILITY STUDENTS ON ELEARNING EDUCATION IN ASEAN COMMUNITY (Proceedings of International Conference on Special Education, 2015)
More than a decade ago, internet had gradually come to play a major role in the world as it was an advance technological tool provided various benefits to human being. Internet could also influence in educational field because it was the advance media to create distance learning in term of online learning or eLearning, which could allow students in different locations to join the same class in the same time. Therefore, many universities and colleges worldwide have turned to focus on eLearning class instead of traditional class. ELearning could also benefit to whole ASEAN community as it is the mode of education allows students in all 10 countries to study together as well as to improve educational standard for whole community. ELearning also help people with disability in ASEAN to access learning easily and help them to fulfill their education requirement. However, even though eLearning is the mode of education allowed everyone to access, but people with disability still face difficulty to access the eLearning websites as equal as ordinary students. So, in order to create equality for all students in ASEAN to gain benefit from eLearning mode of studying, all eLearning websites should be focused on the issue of accessibility to facilitate students with disability. This paper therefore would be proposed the factors to create effective eLearning for education in ASEAN, and necessary components required to create accessibility of eLearning for disability students in ASEAN. This paper could summarize that there were four factors to create effective eLearning for education and the eLearning website must consists of four components to support disability students.